Analisis Pengaruh Faktor Promosi, Pengetahuan Produk, Dan Kualitas Pelayanan Pt Pegadaian Syariah (Persero) Terhadap Minat Untuk Menggunakan Tabungan Emas Syariah (Studi Kasus Pada Masyarakat Kota Jambi) - Neti Amelia; Nurida Isnaeni; Ridhwan . (JOURNAL OF SHARIA ECONOMICS, 2025)
This study is entitled "Analysis of the Influence of Promotion Factors, Product Knowledge, and Service Quality of PT Pegadaian Syariah (Persero) on Interest in Using Gold Savings (Case Study in Jambi City Society)". This study aims to analyze the Promotion Factor (X1), Product Knowledge (X2), and Service Quality (X3) have a significant effect on (Y) the interest of Jambi city society to use Gold savings products at PT Pegadaian Syariah (Persero) Jelutung Branch, Jambi City. This study uses quantitative research with quantitative analysis, primary research data is collected directly from the source in the form of questionnaires, interviews, observations, and documentation taken using purposive sampling techniques with a population and sample of 100 people in the Jambi city community. The method or technique of data collection used is field research. The study uses validity and reliability testing and uses data analysis techniques that include classical assumption tests and multiple linear regression analysis. The results of the study show that the influence of the promotion variable (X1) has a positive effect on public interest in using Gold Savings, the product knowledge variable has a positive effect on public interest in using Gold Savings, and the service quality variable (X3) has an effect on public interest in using Gold Savings.